The effects of sex, season, and natural sunlight on plasma vitamin D3 levels in two chelonian species (Testudo hermanni, Trachemys scripta) and their interaction with calcium, phosphate, and magnesium as associated plasma compounds - Geisler, Gregor; Leineweber, Christoph; Pees, Michael; Öfner, Sabine; Marschang, Rachel E. (Frontiers in Amphibian and Reptile Science, 2023)
Species specific physiology, seasonal changes, sex, and husbandry factors all influence the blood chemistry of chelonians, including vitamin D3, calcium, phosphate and magnesium levels. Problems in the supply of many of these are commonly seen in captive reptiles. The goal of this study was to measure vitamin D3, calcium, phosphate and magnesium in plasma from captive, healthy, adult Hermann’s tortoises (Testudo hermanni) and pond sliders (Trachemys scripta). Samples were categorized and compared based on species, sex, season, and access to sunlight as a central husbandry element. Blood samples of 522 Hermann’s tortoises and 188 pond sliders, taken from March to September 2022, were included in the study. New reference intervals for vitamin D3, calcium, phosphate and magnesium were established, with specific reference intervals calculated for each species, sex, and season in those cases in which significant differences were found based on these factors. For the calculation of reference intervals for vitamin D3 the factors species, season and access to sunlight were considered. Vitamin D3 levels differed by access to sunlight in some seasons depending on the species and were generally higher in Hermann’s tortoises. Plasma vitamin D3 levels did not correlate with calcium, phosphorus or magnesium levels on a larger scale in either species. Calcium, phosphate, and magnesium were higher in females than in males of both species, and magnesium was higher in Hermann’s tortoises than in pond sliders. Our results can be helpful in a more specific interpretation of blood results and support previous findings that direct sunlight is an important factor in chelonian health. More studies are needed to better understand the role of other hormonal influence on the vitamin D3, calcium, phosphate and magnesium metabolism in chelonians.